Use, Perceptions, and Barriers to Water Conservation Strategies for Florida Water Utilities - Shirish Rajbhanary; Tatiana Borisova; Damian Adams; Dwayne Haynes; Chris Boyer (EDIS, 2010)
FE851, an 18-page illustrated report by Shirish Rajbhanary, Tatiana Borisova, Damian Adams, Dwayne Haynes, and Chris Boyer, presents the results of a 2009–2010 survey of representatives of Florida’s drinking water systems to examine the relative use of conservation strategies by Florida water utilities. Includes references. Published by the UF Department of Food and Resource Economics, September 2010.